Preparation of a new filament based on polyamide‐6 for three‐dimensional printing. Issue 12 (3rd February 2017) - Jia, Yunchao; He, Hui; Peng, Xiaodong; Meng, Shuna; Chen, Jian; Geng, Yi
Abstract : Fused deposition modeling (FDM) is one of the trendiest three‐dimensional printing (3DP) technologies. However, FDM products based on virgin polyamide‐6 (PA6) are seriously warped due to the accumulation of shrinkage stress generated from the crystallization of PA6. To solve this problem, maleic anhydride grafted poly(ethylene 1‐octene) (POE‐g‐MAH) is added into PA6 to disturb the crystallization and reduce the shrinkage stress. Besides, rigid polystyrene (PS) with good flowability is further introduced to PA6/POE‐g‐MAH blend because too much addition of POE‐g‐MAH will weaken the PA6/POE‐g‐MAH, which will interrupt the printing process. The POE‐g‐MAH and PS both act as amorphous phase in the blends, which will reduce the shrinkage stress and is helpful to the shape stability of the printed products. Finally, a new kind of PA6‐based filament with good toughness for FDM is prepared via this facile method. POLYM. ENG. SCI., 57:1322–1328, 2017. © 2017 Society of Plastics Engineers